(untitled) (Revista de Ciências Agroveterinárias, 2018)
The objective of this work was to evaluate the potential of rooting and acclimatization of semi-woody cuttings of different rootstocks of Prunus spp. (I-93-38, I-93-27, I-67-57-14, I-67-55-13) e Prunus persica (I-67-54-12), both originating in North America. Semihardwood cuttings were prepared with 15 cm maintaining a couple of whole leaves in the apical portion were conditioned in trays with fine vermiculite and kept under intermittent mist for 50 days. Cuttings ready to be transplanted were placed in ‘citropotes’ containing 2 L commercial Carolina® substrate and kept in acclimation for 60 days. It was observed that the percentage of rooted cuttings was higher for genotype I-93-27 (66.66%), not differing from genotypes I-67-55-13, I-67-54-12 and I-67- 57-14, with 57.77%, 52.22% and 44.44% of rooted cuttings, respectively, this cultivar also recorded the average length of three major roots (4.74 cm) to the average number of roots per cutting, the highest values were observed in I-93-27 genotypes (20.35) and I-67- 57-14 (23.65). It was also observed that the average percentage of transplanted and acclimatized stakes were higher for genotype I-93-27 (72.22%) compared to the others. The I-67-55-13 genotype showed better results for all variables, and more established plants after acclimatization.